2019
DOI: 10.1002/elps.201900325
|View full text |Cite
|
Sign up to set email alerts
|

A novel microchip‐based imaged CIEF‐MS system for comprehensive characterization and identification of biopharmaceutical charge variants

Abstract: A microfluidic system has been designed that integrates both imaged capillary isoelectric focusing (iCIEF) separations and downstream MS detection into a single assay. Along with the construction of novel instrumentation and an innovative microfluidic chip, conversion to MS‐compatible separation reagents has also been established. Incorporation of 280 nm absorbance iCIEF‐MS analysis not only permits photometric quantitation of separated charge isoforms but also facilitates the direct monitoring of analyte focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…These approaches are currently limited to regular CE-SDS and do not include chip-based formats. However, recent progresses in microchip-based CIEF-MS [ 49 ] raise hope that similar successes may be achieved with MCE-SDS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches are currently limited to regular CE-SDS and do not include chip-based formats. However, recent progresses in microchip-based CIEF-MS [ 49 ] raise hope that similar successes may be achieved with MCE-SDS.…”
Section: Resultsmentioning
confidence: 99%
“…Commonly, the peak identity is confirmed by mass spectrometry (MS) [4,[48][49][50]. MCE-SDS and CE-SDS in general are considered as incompatible with MS due to the intrinsic properties of the employed gel matrix.…”
Section: Validation Of Peak Identitymentioning
confidence: 99%
“…The results obtained correlated with standard icIEF-UV profiles. In addition, Mack et al also showed charge variant analysis of mAbs by coupling microchip icIEF with MS [41]. In a comparison between cIEF and CZE, cIEF offered superior performance for pI analysis, while CZE was better for routine and rapid charge heterogeneity analysis [42].…”
Section: Charge Heterogeneity Analysismentioning
confidence: 99%
“…Microfluidic CE-based methods have also been reported for charge variant analysis of mAb products [41,45,46] Online ESI-MS was demonstrated for intact mAb charge heterogeneity analysis with major C-terminal lysine variants separated with an average resolution of 0.8 along with the minor acidic and basic species. The study also identified the glycosylation patterns of the 0-lysine, 1-lysine, and 2-lysine variants [45].…”
Section: Charge Heterogeneity Analysismentioning
confidence: 99%
“…Developing microchip-based cIEF-MS is also very attractive to pharmaceutical industry. Recent microchip-based cIEF-MS system developed by Mack et al provided real-time optical monitoring of focusing and mobilization process of cIEF, good resolving power and high throughput (15 min each assay) for characterization of mAb charge variants (Mack et al, 2019). Besides a direct coupling of cIEF and ESI-MS, cIEF has also been coupled to CZE-MS using a mechanical valve or a nanoliter valve for high-resolution characterization of intact proteins and mAb charge variants (Hühner et al, 2017;Montealegre and Neusüß, 2018).…”
Section: Automated Cief-esi-ms For Top-down Characterization Of Hydrophobic Proteins Urinary Albumin and Mab Charge Variantsmentioning
confidence: 99%